PHYSIOTHERAPEUTIC APPROACH TO SCIENTIFIC CHANGES INVOLVED IN AXILLARY WEB SYNDROME: A CASE REPORT - Carmo, Karla Ferreira do; Lemos, Nayara Alves de Freitas; Freitas-Junior, Ruffo; Faria, Suzana Fonseca Coelho e; Aidar, Osvaldo de Alcântara Braga; Cardoso, Débora Sara de Almeida; Araújo, Mosiah; Botti, Juliana (Mastology, 2021)
Objective: The aim of this study was to discuss the physiotherapeutic approach to around the scar tissue release in a patient with axillary web syndrome (AWS). Methods: A case report was conducted at the Mastology Program Outpatient Clinic of the Hospital das Clínicas/CORA (Advanced Center in Breast Diagnosis) at the Federal University of Goias. The study was approved by the Ethics and Research Committee of CEP-HC/UFG (opinion Nº 4,217,374), and the participant signed an informed consent form. Case description: A 71-year-old patient was included in the 5th postoperative (PO) period with modified radical mastectomy and left axillary lymphadenectomy for the treatment of breast cancer. She was referred to the physiotherapy service due to edema, pain, and associated to around the scar retraction. The restriction of movement of the homolateral limb was diagnosed with AWS. The approach included manual therapy through tissue mobilization, combined with lymphatic drainage and the use of functional bandages in the surgical plastron and cord region. Result: After three sessions, there was an improvement in edema and to around the scar retraction, gain in amplitude, and reduction in pain, regardless of the presence of a single fibrous cord. Conclusion: Tissue release through techniques aimed at myofascial mobilization, associated with complementary therapies, improved the malleability of the tissue, organized the deposition of collagen fibers, and lubricated the connective tissue, preventing and treating fibrosis, the factors involved in the etiology of SARS. This physiotherapeutic approach in the immediate PO proved to be beneficial in limiting dysfunction and optimizing recovery. More research is needed to understand the clinical aspect and possibilities of interventions related to AWS.